If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(x-6)=4x+4=
We move all terms to the left:
5(x-6)-(4x+4)=0
We multiply parentheses
5x-(4x+4)-30=0
We get rid of parentheses
5x-4x-4-30=0
We add all the numbers together, and all the variables
x-34=0
We move all terms containing x to the left, all other terms to the right
x=34
| 3x3=-3 | | 40-8w+4=6w-24+4w | | 16×22=y | | -2x+4(6+3x)=28+6x | | 2/3(3x+9=-2(2x+6) | | 10(n+2)=-150 | | 2x-1=2x-3 | | 18x−1=-19 | | 7/x=11/3 | | 2x+0=9x+8 | | 108=-6x-6 | | -3(h−8)=3 | | 3(2x+9)=-24+3 | | -a+4+3a=-4 | | -7x+8x=2x+4 | | 9x=10-3(5x-6) | | 4(3x+9)=-14+26 | | x(15+8+180+x)=13000 | | 18=3(k−11) | | 7/12=k/8 | | -8=-4(w−14) | | 6y+14=36 | | d+5d=12 | | 5u-8=-33 | | 3.5=x(x+3) | | 6z/7-5z/9=1 | | -8+p/3=-4 | | 64x2-48x=183 | | 8+p=-2p+3 | | 5(x+12)=1/2(7+10x) | | 1/2x+1/10x+1/20x)-x=35,000 | | -5b-6+4b=0 |